Variation in the structure of microbial communities associated with different alfalfa (Medicago sativa L.) cultivars - Zhou, Juan; Li, Jiahao; Dang, Shizhuo; Zhao, Xiaoyan; Li, Meihua; Gao, Yingdong (Frontiers in Microbiology, 2026)
The rhizosphere is a critical zone for root–soil–microbe interactions, and plant species play a major role in shaping its microbial community structure. Alfalfa (Medicago sativa L.), a widely cultivated forage crop with high nutritional and economic value, serves as an ideal model for studying cultivar-specific rhizosphere microbiomes. Using high-throughput sequencing, this study aimed to analyze the rhizosphere microbial communities of seven alfalfa cultivars. A total of 27,878 bacterial OTUs and 5,380 fungal OTUs were identified across all samples. The dominant microbial phyla included Actinobacteria and Proteobacteria (bacteria) as well as Ascomycota (fungi). Although the overall microbial community composition was broadly similar across cultivars, some subtle differences were observed. Key bacterial genera such as Bacillus, Arthrobacter, Nocardioides, and Gaiella were abundant in the rhizosphere. Notably, the cultivars ‘JN7’ and ‘QJ’ exhibited higher overall microbial abundance than the other cultivars. Soil properties were found to differentially influence microbial abundance across the cultivars. Specifically, soil organic matter, total nitrogen (TN), and total phosphorus (TP) significantly affected bacterial abundance, whereas TP, TN, and available phosphorus were the key drivers of fungal community variation. Network analysis revealed stronger co-occurrence relationships among bacterial taxa than among fungal taxa, and predominantly positive associations were detected. This study provides insights into alfalfa cultivar-associated rhizosphere microbiomes and lays a foundation for the development of targeted biofertilizers and optimized cultivation strategies.